Modeling and Simulation as a Bridge to Advance Practical and Theoretical Insights About Forced Migration Studies. (September 2021) - Frydenlund, Erika
Modeling and Simulation (M&S) is a relatively unused research approach in forced migration studies. In most of its application areas, M&S is applied in several broad thematic policy-oriented topics: predicting human movement, humanitarian logistics, communicable diseases, healthcare, policing, and economics. More recently, there has been increased use of M&S in predicting human movement and health impacts resulting from climate change. Computer modeling has benefits for both policy and theoretical advancements in the field. M&S is often associated as a predictive tool that appeals to policymakers and planners. But M&S has many other significant benefits. For policymakers and planners, M&S provides a simulated environment to explore "what-if" scenarios. These scenarios can be adjusted to reflect different assumptions and conditions in the field. M&S can provide a means for translating interpretivist research findings—themselves rich in descriptions of actors, relationships, and dynamics—into visual artifacts that can communicate results to policymakers. It also can help to test the assumptions of theoretical findings, explore generalizability to other cases and conditions, and inform future data collection efforts. On the other hand, because models can take a long time to construct and test, they cannot provide rapid insights about evolving situations to inform decision-making at the onset of a new emergency. Data dashboards, the staple of modern humanitarian operations, are better for identifying emergent needs and tracking efforts. However, modeling what we know from one situation allows us to use those insights in systematic and strategic ways to improve operations for the future. M&S can also provide researchers with an additional tool that allows improved integration of multiple data types and sources. These data, assumptions, and theoretical constructs can be linked together in a complex, nonlinear, dynamic system that can then be set in motion to see if the simulated world reveals phenomena that are witnessed in the real world. But interdisciplinary communication and collaboration is hard and finding modelers who value interpretivist research can be even harder. M&S is not a silver bullet but provides a unique approach that incorporates dynamics and is becoming increasingly accessible to policymakers, practitioners, and academics, including those without computer programing experience. For policy, it is important to invest the time and resources to develop simulation models—from simple to complex—that help when planning for the evolution of events, or for the next event. Models of current refugee situations should inform where to concentrate efforts to advance durable solutions and how to plan for potential scenarios of return to countries of origin. Policymakers must recognize the long-term value of modeling what we know now to use later. Researchers of migration should become familiar with M&S paradigms so they can become part of the model design, development, and testing phases—at least part of the conversation. Better integration of migration scholars in design and development has the potential to strengthen models for policymaking, but perhaps more importantly, to strengthen the field by serving as an extra tool for testing theories, assumptions, and generalizability of findings to other locations and situations.